Effects of entomopathogenic fungus (metarhizium anisopliate) on the termite (coptotermes curvignathus) - Hoe, Pik Kheng (2010)
Coptotermes curvignathus (BLATTODEA: Rhinotermitidae) is a major termite pest in the oil palm plantations on peat as it attacks the living tissues of the plants. Biological control using Metarhizium anisopliae in the peat area has potential for termite control due to its advantages such as environmental friendly and non-hazardous to human health compared to chemical measures. In this study, several isolates of M. anisopliae was obtained from both peat and mineral soils and screened for their pathogenic effect on C. curvignathus. Five potential isolates (TA, LR2, MG, CI and AR3) had been further characterised and evaluated for their pathogenicity activity and investigated for their mode of action. There was also no repellent effect of the termites towards the isolates. Among the five isolates isolate TA had the most potential, followed by isolate LR2 and the least potential was isolate CI. Isolate TA which was obtained from peat soil, had the highest virulence and exhibited the quickest sporulation at 2 days post inoculation. The ultra structural studies revealed that isolate TA was able to have a higher virulence level compared to other isolates was due to its quick germination and penetration (within 3 hours) of the mycelia into the termite body, where the colonization of mycelia happened subcutaneously. Between isolate TA and LR2, isolate TA that germinated and penetrated into the termite more quickly. Isolate CI was the least virulent as this was the only isolate that did not spread subcutaneously; hence, it was very likely that the mycelia would have been groomed off before they were able to penetrate. The total mortality of the termites was not only due to the infection of the isolates, but also due to the induced alarm behaviour by the isolates among the termites causing them to be buried or cannibalized the weakened or infected member. Direct applications, like drenching and topical application were very effective but not practical for field application, unless the termite nests or colony can be identified in the peat area. Hence, with a potential isolate like isolate TA and LR2, successful biological control for termites, C. curvignathus, for oil palms on peat can be achieved. However, enhancement of the potential isolates and a suitable application method can augment the effect of the isolates during the field applications.